PENINGKATAN KINERJA GURU SEKOLAH DASAR MELALUI MANAJEMEN KEPALA SEKOLAH - amin efendi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
Teacher is the most important factor in Education, because the teacher is as the facilitator for the students in learning process to achieve the goal of education (instructional, institutional, national). A teacher will be able to teach optimally if there is a role of the headmaster in managerial. Therefore, the headmaster must be able to stimulate the teachers in order to increase their performance. Headmaster’s good management plays a crucial role in increasing teacher’s competence.